Comparison between Two Different Fractal Koch Position for Reflecting Intelligent Surface (RISs) - MOHD YAZIZ, NUR SYAHIRAH; A. RAHIM, MOHAMAD KAMAL; SAMSURI, NOOR ASMAWATI; ZUBIR, FARID (ELEKTRIKA- Journal of Electrical Engineering, 2024)
The paper focuses on investigating the fractal shape placement of metasurface reflectors at the X-band frequency for Reflecting Intelligent Surface (RIS). The proposed reflector adopts a square shape, with the fractal intersection on a Rogers RO5880 substrate measuring 0.51 mm in thickness. The graph illustrating the S-parameter and reflection phase exhibits the simulated outcomes for various fractal positions. Furthermore, the bandwidth of the proposed reflector was determined by analyzing the simulation results. The impact of the incident wave angle on the proposed reflector was observed to shift along the horizontal axis. Mainly, the reflector with the inward fractal shape position demonstrated better performance and a wider bandwidth compared to the outward fractal substrate.